Tragal Cartilage Versus Polytetrafluoroethylene (TEFLON) Partial Ossicular Replacement Prosthesis (PORP): A Comparative Study of Outcomes of Ossiculoplasty - Pathan, F.; Satpathy, S.; Bhalekar, S.; Sudarshan, K. (International Journal of Innovative Research in Medical Science, 2016)
Reconstruction of the conductive mechanism of the middle ear is one of the most intriguing topics in middle ear surgery. An implant in middle ear should be safe, biocompatible, stable, easily insertable and capable of yielding optimal sound transmission. A comparative prospective study of 50 patients each of ossiculoplasty between tragal cartilage, and polytetrafluoroethylene (teflon) partial ossicular replacement prosthesis (PORP) to analyse the hearing gain at the end of six months between cartilage ossiculoplasty and Teflon PORP(Partial Ossicular Replacement Prosthesis). In our study it was observed that the degree of post-operative hearing improvement when cartilage was used as a ossiculoplasty material was consistently more than when PORP was used which was statistically significant.